Pengaruh Kinerja Keuangan Terhadap Permodalan Bank Syariah Mandiri - Siti Fahraheda Nur; Parno Parno; Dedy Mainata (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2022)
The financial performance seen through the ratio calculation has a relationship to the capital of Islamic banks. Bank Syariah Mandiri as the largest Islamic bank in Indonesia is a benchmark for the Islamic banking industry in Indonesia. The purpose of this study is to see the relationship between financial performance and capital adequacy of Bank Syariah Mandiri. By using secondary data from 2015-2019 and performing classic assumption tests, multiple linear regression tests, and hypothesis testing, the results showed that ROA had no significant effect on CAR. FDR has a significant negative effect on CAR. BOPO has no significant effect on CAR. NIM has no significant effect on CAR. NPF has a significant negative effect on CAR. The results of multiple linear regression analysis simultaneously show that ROA, FDR, BOPO, NIM, NPF simultaneously affect CAR